Konsep Pertobatan Menurut 2 Korintus 7: 8-11 - Foriaman Zega; Hendi H (Institut Agama Kristen Negeri Tarutung, 2020)
AbstractRepentance is the second thing we do after we believe and are baptized into Christ Jesus. Repentance means transforming the salvation every day and becoming a lifestyle of believers. Repentance will continue to perfect the image of God in us becoming more and more like God or Christ. And in the end the believers will be united in God (Theosis) by the grace of God. Therefore, the issue of repentance is important to discuss so that every believer can understand this doctrine and practically could do it in his life with Christ. Repentance always starts from sorrow or tears for the sins committed. This tears is the basis of the repentance described by the Apostle Paul in 2 Corinthians 7: 8-11. Then repentance and tears will continually purify our sinful nature to be like Christ likeness. This paper will study the theory or concept of repentance according to the Apostle Paul and will be supplemented by Patristic literature or the Fathers of the Church’s concept.Keywords: Repentance; tears; salvation; theosis; nous.AbstrakPertobatan adalah hal kedua yang kita kerjakan setelah kita percaya dan dibaptis dalam Kristus Yesus. Pertobatan berarti mengerajakan keselamatan kita setiap hari dan menjadi gaya hidup orang percaya. Pertobatan akan terus menyempurnakan gambar Allah di dalam diri kita menjadi semakin serupa dengan Allah atau Kristus. Dan pada akhirnya kita akan menyatu di dalam Allah (Theosis) oleh anugerah Allah. Sebab itu masalah pertobatan ini penting dibahas supaya setiap orang percaya dapat memahami hal ini dan secara praktis dapat mengerjakannya dalam kehidupannya bersama Kristus. Pertobatan selalu dimulai dari dukacita atau kesedihan akan dosa-dosa yang dilakukan. Dukacita ini adalah dasar pertobatan yang dijelaskan Rasul Paulus di dalam 2 Korintus 7:8-11. Selanjutnya pertobatan dan tangisan dikerjakan untuk semakin hari semakin serupa dengan Kristus. Tulisan ini akan mengkaji teori atau konsep pertobatan menurut Rasul Paulus dan akan dilengkapi dengan literarur Patristik atau para Bapa Gereja.Kata Kunci: pertobatan; dukacita; keselamatan; theosis; nous .